Analysis of the Effect of Company Size on the Effective Tax Rate in Manufacturing Companies Listed on the Indonesia Stock Exchange (IDX) - Abdullah Rizky; Yaasiinta Wardiatun; Aprilliana Puspita; Adinda Rahmawati; Arya Dwi Saputra; Septyana Puji (ProBisnis : Jurnal Manajemen, 2025)
This study aims to analyze how firm size affects the effective tax rate (ETR) of manufacturing companies listed on the Indonesia Stock Exchange (IDX). Using additional data from 54 businesses in the food and beverage subsector for the 2024 period, a quantitative research methodology was employed. Using SPSS software, basic linear regression was used to analyze the data. The analysis results indicate that firm size negatively impacts the effective tax rate; however, this effect is not statistically significant, with a significance value of 0.010 (>0.05). Only 12.2% of the variation in the effective tax rate can be explained by firm size, while the remainder is influenced by factors outside the model, based on a coefficient of determination (R2) value of 0.122. The study results indicate that the effective tax rate paid decreases with firm size, although this is not statistically significant. This finding is consistent with several previous studies that concluded that the ETR is not significantly affected by firm size. Thus, it can be concluded that the effective tax rate for manufacturing companies in the Indonesian food and beverage subsector is not primarily determined by firm size.